Kajian Potensi Daur Ulang Sampah Makanan Restoran di Kota Padang - Yommi Dewilda; Rizki Aziz; Mhd. Fauzi (Fakultas Teknik, 2019)
The purpose of this research is to study the recycling potency of food waste from restaurants in Padang City by measuring the food waste generation and its composition. Sampling and analysis were carried out based on SNI 19-3964-1994. It was performed for eight consecutive days at fifteen different sampling locations which include restaurants, cafes, fast food, and food courts. The result of this research showed that the average generation unit of restaurant food waste in the city of Padang was 0.105 kg/cap/day in weight units or 0.955 liters/cap/day in unit volume. The total generation of restaurant food waste was 132 liters/day which consists of organic waste (food scraps, leaves, fruit skin, vegetables, eggshells, bones), plastic (plastic bottles, packaging, bags, straws, and spoons), paper (tissue, packaging paper, paper containers, cartons), and others (styrofoam, broken glass, smoked cigarette remains, cans, glass bottles). Organic waste has the largest percentage by the composition of 70.69%, and that of plastic was at 11.35%. The study further showed that the recycling potency of restaurant food waste in Padang City was made up of 7.65% paper, 51.32% plastic, 59.86% glass, 100% nonferrous metal and 91.71% organic waste. Conclusively, recycling and composting method were recommended to process the restaurant food waste.